PELATIHAN PEMBUATAN PRODUK DIVERSIFIKASI PELEPAH PISANG BAGI WARGA DESA DUWET KAB.MALANG - Ellyn Eka Wahyu; Yekie Senja Oktora (P3M Politeknik Negeri Malang, 2024)
Banana fronds or Gedebog in Javanese, banana fronds are one part of the banana tree that is rarely 'touched', even though banana fronds themselves contain many vitamins and are rich in health benefits. Therefore, it is feasible to increase the value of the product and its selling value so that it can be enjoyed by the wider community as a healthy snack product through diversification of banana fronds into banana frond chips that can be accepted by the community. Duwet Village as a good banana producing village, has not yet understood the diversification of products that can be processed from banana fronds. The methods used in this activity are a) Initiation of PPM Activity Program, b) Transfer of Knowledge, c) Discussion and Q&A, d) Problem Discussion. The training participants were mothers of Duwet villagers who were housewives, farmers, and who did not have a fixed income. The results of this activity found several obstacles that not all types of bananas, the fronds can be diversified into banana frond chips, for the process of making this product also has special criteria related to down time production time.